The Duration of Hemodialysis Treatment and comorbidity with Adherence to Fluid Restristion in patient Undergoing Hemodialysis: A Correlational Study - Khumaeroh, Ana (Akademi Keperawatan RSPAD Gatot Soebroto, 2023)
Background: To achieve successful hemodialysis, patients with End Stage Renal Disease (ESRD) must follow comprehensive treatment including: diet, medication use, fluid restriction and presence of hemodialysis. Previous research has identified that fluid restriction is the most difficult regimen to adherence.Limiting fluid intake is very important done For avoid complications excess fluid Which can cause interdialytic weight gain (IDWG) and has an impact on cardiovascular complications such as congestive heart failure, pulmonary edema and even death. Apart from complications due to excess fluid, patients are also at risk of experiencing complications from hypertension, anemia, decreased immunity and nervous disorders . This can influence patient perceptions and impact behavior on compliance with hemodialysis therapy regimens . Another thing that can affect compliance is ongoing psychosocial stress due to having to undergoing hemodialysis therapy for a long time, causing a negative impression or attitude towards fluid restriction management. Apart from that, other research stated that the duration of hemodialysis was correlated with non-compliance with fluid restrictions . Based on this phenomena, researchers are interested in analyzing the relationship between length of time undergoing hemodialysis and comorbidities with fluid restrictions in hemodialysis patients.Purpose : This study aims to determine the relationship between duration of hemodialysis treatment and comorbidity with adherence to fluid restrictions in patients hemodialysis.Methods: This study used a cross sectional design with consecutive sampling on 121 respondents. Data collection with demographic sheets and fluid compliance questionnaires. Next, a bivariate analysis was carried out using Chi-Square .Results : The majority of respondents were in the age range 41-60 years namely 82 respondents , the majority of respondents were men As many as 75 respondents , the education level of the respondents showed that most were at the high school level, around 59 respondent , The majority of respondents had undergoing hemodialysis within a period of 1-5 years. Characteristics respondents other is comorbidity where majority own comorbidity <3 as much as many as 100 respondents. bivariate analysis showed that there was a significant relationship between duration of hemodialysis treatment and adherence to fluid restrictions (p=0.033), however there was no significant relationship between comorbidities and adherence to fluid restrictions (p= 0.560 ) .Conclusion: there is a significant relationship between duration of hemodialysis treatment and adherence to fluid restrictions, but there is no significant relationship between comorbidities and adherence to fluid restrictions. Keywords : End Stage Renal Disease, Hemodialysis , Fluid adherence, comorbidity, Duration of Hemodialysis Treatment